1993
DOI: 10.1128/mcb.13.5.2815
|View full text |Cite
|
Sign up to set email alerts
|

In Xenopus laevis, the product of a developmentally regulated mRNA is structurally and functionally homologous to a Saccharomyces cerevisiae protein involved in translation fidelity.

Abstract: We have performed a differential screen of a Xenopus egg cDNA library and selected two clones (Cli and C12) corresponding to mRNA which are specifically adenylated and recruited into polysomes after fertilization. Sequence analysis of Cll reveals that the corresponding protein is 67.5% identical (83% similar)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…One possible way of testing this model is to examine whether increasing the levels of the translation release factors leads to suppression of selenocysteine incorporation. To perform this experiment, we co-transfected individual reporter constructs together with expression constructs bearing the genes encoding eRF1 and eRF3 (29,30). Comparison with the control construct pBLUGA revealed that there was little specific repression of selenocysteine incorporation associated with the overproduction of the eRFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One possible way of testing this model is to examine whether increasing the levels of the translation release factors leads to suppression of selenocysteine incorporation. To perform this experiment, we co-transfected individual reporter constructs together with expression constructs bearing the genes encoding eRF1 and eRF3 (29,30). Comparison with the control construct pBLUGA revealed that there was little specific repression of selenocysteine incorporation associated with the overproduction of the eRFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid Cl2Al-454,480-559 was made by digesting plasmid Cl2Al-454 with NheI (just upstream of the CPE) and EcoRI (located downstream in the vector); the larger fragment, which contained only a few C12 sequences upstream of the CPE, was filled in with Klenow enzyme and relegated. Plasmids Cl1-3'UTR, Cl1A1-179, CliA1-219, and Cl1lA235-5OSAUUAAA were constructed by PCR using the following oligonucleotides and a subclone of the Cli cDNA (38) sequences of this region (Cl11-179, C11A287-468, and Clil1-219; Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The gel was subsequently electrotransferred onto Hybond-P PVDF membrane (Amersham Pharmacia Biotech), and the membrane blocked overnight at 4°C in 1× phosphate-buffered saline (PBS) containing 3% milk, 2% Normal Goat Serum, and 0.1% Tween-20. Blots were probed with anti-eRF1 serum (a generous gift from Michel Philippe (Université de Rennes I); Tassan et al 1993) in blocking solution at room temperature for 60 min. Blots were washed three times for 15 min in 30 mL of 1× PBS containing 0.1% Tween-20.…”
Section: Western Blotmentioning
confidence: 99%